Cambios climáticos a escala astronómica y milenaria registrados en el Mediterráneo occidental - González-Mora, Beatriz (2008)
[EN]Foraminifer assemblages and geochemistry from ODP site 977A (Alboran Sea) and PRGL1-4 (Gulf of Lions) have been studied to analyse changes in the microfauna, climate and paleoceanography in the Western Mediterranean Sea at several time intervals during the last 250 kyr. The planktonic foraminifer assemblages in the Alboran Sea seem to be mainly controlled by changes in sea surface temperature (SST) and confirm the pervasive millennial variability previously reported with alkenone-based SST. In addition, astronomical variability is also shown by the foraminifer assemblages. The warm substages of stage 7 are recognized by the high abundances of the species Globigerinoides ruber, reflecting oligotrophic conditions and a stratification of the water column, coinciding with the Northern Hemisphere summer insolation maxima. Water stratification is due to surface water warming (density decrease) and coincides with strong seasonality. These oceanographic conditions gradually changed to more vertical mixing and weaker seasonality during cold substages. Neogloboquadrina pachyderma (left coiling) is very scarce during the period studied, suggesting a reduced southward influence of the Polar Front and less extreme cooling at that time. Several possible Heinrich-like events are described in this study. These periods of iceberg discharges from the North Atlantic are recorded in the Mediterranean Sea by low water δ18O values, low salinity, relatively low SST, a decrease in the total number of planktonic foraminifers, and disappearance of Globorotalia inflata and temperate water species. These lighter oxygen isotope and low salinity waters would have caused density stratification. The extremely cold conditions caused an abrupt and drastic decrease in surface productivity. During the period studied four organic-rich layers (ORL) can be recognized. These sediments are related to the sapropels from the Eastern Mediterranean. It may be observed that all the organic-rich layers coincide with low δ18O values in Globigerina bulloides. This relates the formation of these layers to the arrival of isotopically lighter waters. The origin could have been either increased rainfall over the Mediterranean area or a stronger influence of Atlantic waters due to greater inflow to the Mediterranean. The geochemical data suggest that they were formed under stratification conditions and at times of high surface productivity. No organic-rich layer was developed during the 220 kyr-Northern Hemisphere summer insolation maximum due to the occurrence of a possible Heinrich-like event at the same time, however sapropel 8 was formed, suggesting that different factors affect the Mediterranean subbasins in a different way. A reconstruction of SST in the Alboran Sea between 245 and 145 kyr has been made based on the modern analog technique using planktonic foraminifers. We used a modern database that contains a total of 253 samples, 123 from the North Atlantic and 130 from the Mediterranean Sea. For the estimates we used PaleoAnalogs 2.0, computer program developed by the University of Salamanca. Our reconstruction shows a small SST difference between substages 7.3, 7.2 and 7.1. An important millennial variability (7.4, 5.6 and 4.6 kyr) occurs during the whole studied period, both in warm and cold intervals, although changes seem to have more amplitude during cold ones. Seasonality seems to be higher during the warmer substages, 7.5 and 7.3, and smaller during the cold substage 7.4. Mg/Ca paleothermometry and stable isotope measurements performed on tests from the planktonic foraminifers Globigerinoides ruber (white), Globigerina bulloides, and Neogloboquadrina pachyderma (right coiling) have revealed that during marine isotope stages 6 and 7 warm substages were characterized by strong seasonality, thermal stratification of the water column and less surface productivity. By contrast, during cold substages less pronounced seasonality and basin stratification prevailed together with greater productivity. These data also revealed that periods of stratification due to the low salinity of the upper water mass occurred during the formation of organic-rich layers and also during Heinrich-like events. Changes in the benthic foraminifer assemblage (at 200 m depth) between 60-30 kyr have been studied in core PRGL1-4 (Gulf of Lions), and have been found to be strongly controlled by the Dansgaard-Oeschger variability. During stadials, the species most represented were Trifarina angulosa, Astrononion gallowayi, Lobatula lobatula, and miliolids; whereas during interstadials, the assemblage was dominated by Hyalinea balthica, bolivinids, buliminids and agglutinated foraminifers. This suggests more oxygenated bottom waters and a lower organic matter content during stadials, as previously seen for the benthic fauna from the Alboran Sea (2000 m depth). This can be explained in terms of enhanced basin-wide vertical mixing caused by stronger winds or of less productivity throughout the Mediterranean basin, due to a reduced nutrient supply from river discharges. However, during interstadials, both weaker winds and warmer surface waters could have reduced the vertical mixing or a greater nutrient input could have caused an increase in basin productivity. The benthic fauna during Heinrich stadials suggests a similar oceanographic setting to that of the other stadials. In order to better constrain the factors controlling the calcification rate in planktonic foraminifera, and to assess shell weight reliability as an atmospheric CO2 proxy, changes in shell weight in several planktonic foraminifer species (Globigerina bulloides, Neogloboquadrina pachyderma (right coiling) and Globigerinoides ruber (white)) have been studied in core samples from the Alboran Sea (Western Mediterranean) between 250-160 kyr (marine isotope stages 6 and 7). These results suggest that factors controlling calcification rate depend on the species and it is not always related with atmospheric CO2. In Globigerina bulloides and Globigerinoides ruber (white) calcification rate is mainly controlled by atmospheric CO2 and water temperature, whereas Neogloboquadrina pachyderma (right coiling) shell weight is directly related to optimum growth conditions: heavier shell weights coincide with more relative abundance of this species due to optimum temperature conditions. Therefore, foraminifer shell weight should be used carefully as an atmospheric CO2 proxy. Furthermore, Sr/Ca analysis in shells of the same three species of foraminifers were also performed in order to observed interspecific variations and to find out the parameters that control this ratio. Our results show a common, large Sr/Ca variability for the three species studied, thus suggesting changes in the global ocean Sr/Ca ratio as the main cause of variations in shell composition. [ES]Se han estudiado las asociaciones de foraminíferos planctónicos y la geoquímica en muestras del mar de Alborán y el golfo de León) para analizar los cambios en la microfauna, el paleoclima y la paleoceanografía en el Mediterráneo occidental durante los últimos 250 ka. Las asociaciones de foraminíferos planctónicos en el mar de Alborán parecen haber estado controladas principalmente por cambios en la temperatura del agua superficial (SST), lo que confirma la variabilidad milenaria observada en anteriores estudios. Varios posibles eventos Heinrich tuvieron lugar causaron un drástico y rápido descenso en la productividad superficial y una estratificación de la columna de agua por densidad. Además, se han reconocido cuatro capas ricas en materia orgánica cuya formación se relaciona con la llegada de aguas isotópicamente más ligeras causada por un aumento en las precipitaciones sobre la región mediterránea o una mayor influencia de las aguas atlánticas debido a un mayor intercambio a través del estrecho de Gibraltar bajo condiciones de estratificación de la columna de agua y alta productividad superficial. Se han reconstruido las SST en el mar de Alborán basadas en el método de los análogos modernos aplicado a los foraminíferos planctónicos y utilizando la relación Mg/Ca. Ambos resultados son similares aunque la relación Mg/Ca presenta ciertas ventajas. Con el fin de evaluar los factores que controlan la tasa calcificación en los foraminíferos planctónicos y si su peso se puede utilizar como indicador de CO2 atmosférico, se ha estudiado la evolución del peso de los foraminíferos en diferentes especies y parece que dicho parámetro debe ser utilizado con cautela. Finalmente, los cambios en la asociación de foraminíferos bentónicos entre 27 y 57 ka en el golfo de León parecen haber estado controlados fuertemente por la variabilidad milenaria Dansgaard-Oeschger, que pudo haber afectado a la oceanografía de todo el Mediterráneo.